The Influence of Credit Risk on Bank Profitability in Indonesia - Jihan Mafaza; Maharani Dheva Dwi Safitri; Eiyagina Tenika; Henny Setyo Lestari (Universitas KH. Abdul Chalim Mojokerto, 2025)
This study aims to examine the effect of capital adequacy ratio, non-performing loan, loan loss provisions ratio, loan-to-deposit ratio, loan-to-asset ratio, bank size, and bank age on financial performance as measured by return on assets (ROA) in 35 banking companies listed on the Indonesia Stock Exchange during the period 2018-2022. The study results indicate that capital adequacy ratio, non-performing loan, loan loss provisions ratio, and bank size do not significantly affect bank financial performance. On the other hand, loan-to-deposit ratio, loan-to-asset ratio, and bank age were found to significantly impact ROA, indicating that liquidity and company age factors are important determinants in improving banking financial performance.